Differences In The Activity Of Female And Male Students In Guwa Kidul Village Cirebon - Harsela, Chiska Nova (Green Publisher Indonesia, 2019)
The inequality of academic achievement between female students and men in the village of guwa kidul creates anxiety for kuwu. Into a big question mark to be broken. Thus the reason for research on inequality. The method used in this study is a descriptive qualitative in which the research data is described or described. The study is conducted in SMPS al munawaroh village of guwa kidul district kaliwein cirebon district. Studies show that female students who dominate the quantity in schools are able to outperform male academic achievement. However, in non-academic aspects male students are superior. The causes of this are due to female students' greater study, reading, and memorization. Male students, on the other hand, are more adept at lessons that train creativity and skills such as sports and art. Which means they both have their own preeminence toward excellence. The school endeavored to ensure that both objects of research could hone their potential through reading and religious literacy.